2019
DOI: 10.1088/1755-1315/403/1/012057
|View full text |Cite
|
Sign up to set email alerts
|

Constructive and regime parameters of horizontal impact crusher of grain materials

Abstract: In order to ensure the best digestibility of feed, all the nutrients included in their composition should be given to animals in crushed form. Particle size of feed is different for all species and age categories of animals. The most common “shock” crushers give up to 30% of the dust fraction and up to 20% of the underground one. Nowadays, impact and centrifugal-rotor grain crushers that use a “slice-chipping” are the most effective ones. The small-sized horizontal impact crusher, which constructive and techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…where N is the number of simulations. The prediction model Equation (7) in the natural space is derived by combining the factor-coding Equations ( 4) and (6).…”
Section: Rsm Test Scheme Designmentioning
confidence: 99%
See 1 more Smart Citation
“…where N is the number of simulations. The prediction model Equation (7) in the natural space is derived by combining the factor-coding Equations ( 4) and (6).…”
Section: Rsm Test Scheme Designmentioning
confidence: 99%
“…However, the study did not present a clear optimization plan for enhancing crushing efficiency and reducing power consumption. Iskenderov R et al [7] developed a horizontal impact crusher and conducted multifactorial experiments to ascertain the optimal design and operational parameters. They suggested that the designed impact crusher is versatile and can crush various types of feeds by adjusting the operating parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Rotary crushers with hammer 1076 (2022) 012035 IOP Publishing doi:10.1088/1755-1315/1076/1/012035 2 working bodies are considered better than other crushers with high productivity. K.Nwaigwe, C.Nzediegwu, and P.Ugwuoke developed a vertical rotor hammer cassava grinder and substantiated its parameters [20]. H.Zhao and colleagues studied metal and bimetal hammers to determine performance [21].…”
Section: Introductionmentioning
confidence: 99%
“…The development, research and creation of an optimal and efficient way to grind grain feed encourages many researchers to create new designs for shredders [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%